2000
DOI: 10.1034/j.1600-079x.2001.280306.x
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin receptors in human uveal melanocytes and melanoma cells

Abstract: Previous work has demonstrated that melatonin inhibits growth of cultured human uveal melanoma cells. The goal of this study was to determine the expression of mRNA encoding the melatonin receptor subtypes and the effect of specific melatonin receptor agonists on cell growth of uveal melanoma cells and melanocytes. RNA expression of the human melatonin Mel1a and Mel1b receptor subtypes was determined by reverse transcription‐polymerase chain reaction (RT‐PCR) amplification of RNA isolated from two melanoma c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
59
0
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(63 citation statements)
references
References 13 publications
(26 reference statements)
3
59
0
1
Order By: Relevance
“…In contrast, the MT1 receptor was responsible for the enhancement of the tumor suppressing effect of melatonin in MCF-7 breast cancer cells (39,53) and in S-91 murine melanoma cells (45). In uveal melanoma cell lines, melatonin and agonists for MT1 and MT2 inhibited melanoma growth, whereas the nuclear receptor was not involved in growth suppression (47). In estrogen-receptor positive breast cancer cells, the expression of ROR· was found to clearly contribute to melatonin-induced growth inhibition (70).…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…In contrast, the MT1 receptor was responsible for the enhancement of the tumor suppressing effect of melatonin in MCF-7 breast cancer cells (39,53) and in S-91 murine melanoma cells (45). In uveal melanoma cell lines, melatonin and agonists for MT1 and MT2 inhibited melanoma growth, whereas the nuclear receptor was not involved in growth suppression (47). In estrogen-receptor positive breast cancer cells, the expression of ROR· was found to clearly contribute to melatonin-induced growth inhibition (70).…”
Section: Discussionmentioning
confidence: 88%
“…Melanoma is an aggressive form of skin cancer associated with high mortality and limited response to therapy once extended beyond the skin (42)(43)(44). Melatonin has been shown to suppress cell growth in selected cutaneous and uveal melanoma cell lines of rodent and human origin (32,(45)(46)(47). Also clinically, there is some evidence for melatonin having potent antineoplastic activity (48)(49)(50)(51).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such occupations include, among others, farm workers (exposed to pesticides) (7,8), metal workers (exposed to endocrinally active heavy metals and metalworking fluids) (7)(8)(9), welders (possibly exposed to organic solvents and heavy metals) (10), medical and dental workers (potentially exposed to heavy metals and bisphenol A) (7,10), workers in the leather industry (exposure to heavy metals and solvents) (9), and workers in the chemical industry (10). Although epidemiological evidence for exposure to EDC has so far been inconsistent (11)(12)(13)(14), laboratory studies suggest that melanoma cells may be influenced by hormonal factors (15).…”
Section: Behrens Et Almentioning
confidence: 99%
“…120 In another study, the growth inhibitory effect of melatonin was demonstrated at a concentration of 2 nM, the physiological concentration found in aqueous humor; the growth inhibiting effect of melatonin on uveal melanoma cells was shown to be related to activation of MT 1 melatonin receptors. 121 In addition, the antiproliferative effect of melatonin was attributed to the stimulatory action on antioxidative enzyme synthesis. 122 High daytime serum melatonin levels (9.7 to 20.9 pg/mL) was reported in patients with melanoma as compared with normal individuals (1.4 to 2.1 pg/mL).…”
Section: Melatonin In Melanomamentioning
confidence: 99%